A novel algorithm to solve the differential equation describing the non-interactive multiple-trap system model in thermoluminescence. Issue 5 (3rd June 2018) - Caselli, E.; Ortega, F.; Santiago, M.; Marcazzó, J.; Lester, M.; Molina, P.
ABSTRACT: The analysis of glow curves in thermoluminescence requires finding a closed expression for the light emitted as a function of the temperature and the parameters characterizing trap and recombination centers. Since it is not possible to derive a closed expression from the set of coupled differential equations describing the thermoluminescence phenomenon, approximations are made even for the simplest models. All of them resort to an approximation known as the quasi-equilibrium approximation (QE), and to further approximations. In this article, an algorithm is reported that permit the derivation of a closed expression for the emitted light for the model known as the non-interactive multi-trap system (NMTS) model by resorting only to the QE approximation. It is shown that the integration of the first order differential equation related to the NMTS model can be replaced by finding the roots of an analytical expression.